Cultural Transformations Nigerian Women Leading Public Relations - Adi, Ana (Taylor & Francis Group, 2025)
This book is a groundbreaking exploration of the lived experiences of women in Nigeria's public relations industry. It will inspire students, researchers, and professionals to foster greater inclusivity and innovation in communication practices, and will resonate with policymakers and associations focused on equity in the workplace
Description based on publisher supplied metadata and other sources
Keywords: Public relations-Nigeria; Women public relations personnel-Nigeria; Discrimination in employment-Nigeria